NUTRITIONAL INTERVENTIONS IN FRAILTY IN OLDER ADULTS: A NARRATIVE REVIEW ON THE CURRENT EVIDENCE - Vieira,Catarina (2023)
ABSTRACT In recent years there has been an increase in elderly population and frailty. Although there is no universal definition of frailty, the most used is the frailty phenotype defined by Fried et al. (2001). Unbalanced eating habits and/or an inadequate nutritional status are modifiable risk factors for frailty. The aim of this literature review is to analyse the role of nutrition in frailty’s treatment in community-dwelling, institutionalized and hospitalized older adults. Regardless the setting, educational strategies, food fortification, supplementation, multidisciplinary and individualized interventions are important and effective strategies for frailty’s treatment. In community-dwelling older adults, multifactorial interventions that combine nutritional education and supplementation seem to be effective in treating frailty. In institutionalized older adults, multifactorial intervention that include protein-energy, vitamin D, calcium and fiber and physical exercise improves nutritional status and also physical capacity. In hospital setting, the most effective strategy is an individualized approach regarding patients’ favourite foods, additional snacks, the use of oral nutritional supplements or use protein-enriched foods and artificial nutrition when necessary. Further studies are needed in order to establish specific recommendations for the intervention in the prevention and treatment of frailty in older adults.